A systematic review of interventions to support the careers of women in academic medicine and other disciplines - Laver, Kate E (BMJ Open, 2018)
OBJECTIVE: To summarise quantitative evaluations of interventions designed to support the careers of women in academia of any discipline. METHOD: A systematic search of English entries in PubMed, CINAHL and Google Scholar was conducted in September 2017. Methodological quality of the studies was independently assessed by two authors using the Joanna Briggs Institute quality appraisal checklists. Meta-analysis was not possible due to heterogeneity in methods and outcomes; results were synthesised and displayed narratively. RESULTS: Eighteen eligible studies were identified, mostly evaluating programmes in academic medicine departments. The most common interventions were mentoring, education, professional development and/or networking programmes. All programmes took a ‘bottom-up’ approach in that women were responsible for opting into and devoting time to participation. Study quality was low overall, but all studies reported positive outcomes on at least one indicator. Most often this included improvements in self-rated skills and capabilities, or satisfaction with the programme offered. Results regarding tangible outcomes were mixed; while some studies noted improvements in promotion, retention and remuneration, others did not. CONCLUSIONS: This review suggests that targeted programmes have the potential to improve some outcomes for women in academia. However, the studies provide limited high-quality evidence to provide information for academic institutions in terms of the best way to improve outcomes for women in academia. The success of an intervention appears to be undermined when it relies on the additional labour of those it is intending to support (ie, ‘bottom-up’ approaches). As such, academic institutions should consider and evaluate the efficacy of ‘top-down’ interventions that start with change in practice of higher management.